Correlation Baijiu analysis of physicochemical factors, microbial communities and flavor compounds during the piling process of Furou-type Baijiu - Liu, Yanbo; Geng, Huanhuan; Tang, Yanyan; Zhang, Pengpeng; Xu, Mengjiao; Liu, Hongliang; Wang, Yonghua; Li, Huawei; Pan, Chunmei (Frontiers in Microbiology, 2025)
In order to investigate the correlations among physicochemical factors, microbial communities, and flavor compounds during the fermentation process of Furou-type Baijiu, high-throughput sequencing (Illumina MiSeq platform) and Gas chromatography-mass spectrometry (GC-MS) were employed to analyze dynamic changes in microbial composition and flavor profiles. Redundancy analysis (RDA) and Spearman's correlation coefficients were applied to elucidate the interrelationships among these parameters. The results indicated that the relative abundance of Weissella gradually decreased, whereas that of Acetobacter increased over time. The dominant fungal genus shifted from unclassified_o_Eurotiales to Pichia. During the early fermentation stage (0–20 h), microbial community structure was strongly influenced by acidity and starch content. In contrast, at later stages (30 h and 40 h), temperature, moisture, reducing sugar, and pH exhibited greater impacts. The synthesis of alcohols and esters was significantly associated with variations in the microbial community. This study provides a theoretical foundation for optimizing the production process of Furou-type Baijiu.